The Difference in Physical Fitness Levels Between Students Who Walk and Those Who Use Motorized Vehicles to School : A Study of Students at SMA Negeri 11 Tidore Kepulauan - Nuryastuti, Triana; Tinamba, Safri (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to determine the difference between the physical fitness levels of students who walk and ride to school. For physical education teachers, the results of this study can provide information about the importance of physical fitness for students because a good level of physical fitness in students allows them to be productive in carrying out activities so they can go about their days with enthusiasm and can achieve optimal learning outcomes. This research is a comparative research with survey method and data collection using TKJI test including 60 meter running test, sit up, push up, trunk lift, sit and rich, one leg, shuttle run and bleep test. This research was conducted on students of SMA Negeri 11 Tidore Kepulauan. The population is all students of SMA Negeri 11 Tidore Kepulauan totaling 110 students. The sample used in this research is grade XI students with a total of 40 students. The variable in this research is a single variable, namely the underhand passing skills of students of SMA Negeri 11 Tidore Kepulauan. In this research, the distance traveled by students from home to school is not a problem. From the results of research on differences in physical fitness levels, it can be concluded that the level of physical fitness of students walking and riding motorized vehicles to school at SMA Negeri 11 Tidore Kepulauan there is no significant difference in both female and male students. This can be shown from the results of hypothesis testing that the significance value (P Value) is greater than the alpha value (5%) or 0.05 in other words Sig> α (0.100> 0.05) so it is decided that H0 is accepted which means that there is no significant difference between the fitness levels of students walking and riding motorized vehicles to school.